2017
DOI: 10.18805/ijar.v0iof.8453
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of Phalaris minor seeds and its comparison with conventional cereal grains for livestock feeding

Abstract: The aim of the present study was to determine the nutritional value of Phalaris minor seeds in comparison to conventional cereal grains. P. minor seeds had higher ether extract (6.3%), total ash (7.5%), acid insoluble ash (AIA, 4.5%), acid detergent fibre (ADF, 10.2%), cellulose (5.5%), acid detergent lignin (ADL, 2.0%), neutral detergent insoluble crude protein (NDICP, 4.0%) and acid detergent insoluble crude protein (ADICP, 2.7%) content in comparison to conventional cereal grains. The crude protein of P. mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results showed that W H has emerged as a promising alternative to reduce methane production in ruminants. In addtion, Kaur et al (2017) in vitro analysis revealed that the net gas production was the lowest in P. minor seeds (216.37 L/kg DM/24 h). Methane production (L/kg DM/24 h) from P. minor seeds (43.03) were lower than wheat (54.33) and barley (57.35).…”
Section: Resultsmentioning
confidence: 87%
“…The results showed that W H has emerged as a promising alternative to reduce methane production in ruminants. In addtion, Kaur et al (2017) in vitro analysis revealed that the net gas production was the lowest in P. minor seeds (216.37 L/kg DM/24 h). Methane production (L/kg DM/24 h) from P. minor seeds (43.03) were lower than wheat (54.33) and barley (57.35).…”
Section: Resultsmentioning
confidence: 87%
“…Reed canary grass (Phalaris arundinacea L.) (RCG) is cultivated in many European countries and other temperate regions in the northern hemisphere as a domestic ruminant feed (Sheaffer and Marten, 1995;Kaur et al, 2017). In Japan, the growth characteristics and nutritional value of RCG have been studied through practical cultivation in the field and measurement of its chemical composition and digestibility (Tokita et al, 2001).…”
Section: Introductionmentioning
confidence: 99%